Mixed methods to explore factors associated with the decline of patients in the methadone maintenance treatment program in Shanghai, China - Lei Zhang; Jiayi Bao; Amy Harrington; Xiaoduo Fan; Zhen Ning; Jingying Zhang; Daqing Shi; Manji Hu; Zhirong Zhou; Zhengyi Cai; Min Zhao; Jiang Du (BMC, 2019)
Abstract Background This study was to characterize the Methadone Maintenance Treatment (MMT) in Shanghai, China, and to explore factors associated with the decline of patients in MMT during 2005-2016. Methods Both qualitative and quantitative methods were used in this study. Based on the data from Shanghai Centers for Disease Control (CDC), we described the changes in the number of patients who received MMT, and new enrollment each year from 2005 to 2016. Focus groups were conducted with 22 patients, and in-depth interviews were conducted with 9 service providers. Results Quantitative data demonstrate that the number of new enrollment began to decline in 2009, and the number of patients receiving MMT began to decline in 2012. The main reasons for dropout include (1) discontinuing medication due to unknown reasons (25%), (2) criminal activities other than drug-related crimes (20%), (3) relapse to heroin use (16%), and (4) physical disease (10%). Qualitative assessment results indicate that the major reasons for the decline of patients in MMT are as follows: (1) the increase of Amphetamine-type stimulants (ATS) use in recent years, (2) limited knowledge about MMT in both patients and MMT staff, (3) complicated enrollment criteria, and (4) discrimination against drug use. Conclusion Various reasons to explain the decline of patients in MMT in Shanghai, China, were identified. Government agencies, service providers, and other stakeholders need to work together and overcome identified barriers to support MMT programs in China.